2017
DOI: 10.1051/epjconf/201715000013
|View full text |Cite
|
Sign up to set email alerts
|

Online Data Reduction using Track and Vertex Reconstruction on GPUs for the Mu3e Experiment

Abstract: Abstract.The Mu3e experiment searches for the lepton flavour violating decay μ + → e + e − e + , aiming to achieve a sensitivity of 2 · 10 −15 in its first phase and ultimately aspiring to a final sensitivity of 10 −16 . During the first phase of the experiment, a muon rate of ∼ 10 8 μ/s will be available, resulting in a data rate of ∼ 80 Gbit/s. The trigger-less readout system is based on optical links and switching FPGAs sending the complete detector data for a time slice to one node of the filter farm. A fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Selected data frames get written to disk with a reduction factor ∼100. We showed that with commercial GPUs available today, and an optimized reconstruction algorithm [8], this reduction factor can be achieved with a 98% reconstruction efficiency [9] for signal events in the acceptance of the detector.…”
Section: Data Acquisition System and Reconstructionmentioning
confidence: 99%
“…Selected data frames get written to disk with a reduction factor ∼100. We showed that with commercial GPUs available today, and an optimized reconstruction algorithm [8], this reduction factor can be achieved with a 98% reconstruction efficiency [9] for signal events in the acceptance of the detector.…”
Section: Data Acquisition System and Reconstructionmentioning
confidence: 99%
“…As it is not possible to store all the data produced by the detector, the online filter farm will be used to reduce the data rate by performing a full reconstruction of each frame [5]. To cope with such high rates and be able to fully reconstructed each frame Mu3e will use the novel 3-dimensional Multiple Scattering (MS) triplet fit [7].…”
Section: Reconstructionmentioning
confidence: 99%
“…All other R&D efforts are intended for future experiments or upgrades. In most proposals, data from a single sub-detector is analyzed on the GPU at a significantly lower data rate than 40 Tbit/s [9][10][11]. For some, the GPU coprocessor performs track reconstruction, but event selection or data reduction occur on x86 CPUs [10].…”
Section: Introductionmentioning
confidence: 99%
“…For some, the GPU coprocessor performs track reconstruction, but event selection or data reduction occur on x86 CPUs [ 10 ]. In other cases, event selection for a single physics signature runs on the GPU [ 9 , 11 ]. For Run 3, ALICE plans to perform track reconstruction of more than one subdetector and data compression on the GPU, at a data rate of 5 Tbit/s [ 12 ].…”
Section: Introductionmentioning
confidence: 99%